2009
DOI: 10.5650/jos.58.607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Functional Groups on Incorporation Behavior of Amino Acid-Type Surfactant into Phospholipid Vesicle Membrane

Abstract: The incorporation behaviors of some N-dodecanoyl amino acid-type surfactants into L-adipalmitoylphosphatidylcholine (DPPC) vesicles in aqueous solution were investigated. From the leakage measurements of a vesicle-entrapped fluorescence probe, it was found that these surfactants did not affect the DPPC vesicle so much at a very low concentration less than a one-tenth of the critical micelle concentration (CMC), but caused a significant release of the probe form the vesicles even at just below the CMC. The leak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…On the other hand, our present results demonstrate that SDS micelles and monomers can solubilize relatively large, 120 nm diameter vesicles that have some degree of membrane curvature. This finding is consistent with a few past studies , that also indicate that SDS micelles and monomers can solubilize ca. >120 nm diameter vesicles.…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, our present results demonstrate that SDS micelles and monomers can solubilize relatively large, 120 nm diameter vesicles that have some degree of membrane curvature. This finding is consistent with a few past studies , that also indicate that SDS micelles and monomers can solubilize ca. >120 nm diameter vesicles.…”
Section: Resultssupporting
confidence: 93%
“…In 2009 we identified more than 400 articles after searching Web of Science, PubMed, SciDir and OVID databases using ‘isothermal AND titration AND calorimetry’ or ITC or ‘Isothermal Titration Calorimetry’ search terms. These have been classified into the following categories: Pre‐2009 references cited in the text and review articles 1–43 Protein‐protein and protein‐peptide interactions 44–124 Protein/peptide‐small molecule interactions 125–218 Protein/peptide‐metal ion interactions 219–253 Protein/peptide‐nucleic acid interactions 254–273 Protein/peptide‐lipid interactions 274–292 Protein/peptide‐polysaccharide interactions 293–316 Nucleic acid‐small molecule interactions 317–348 Small molecule interactions …”
Section: Introductionmentioning
confidence: 99%
“…An important consequence of incorporating NASTs into phosphatidylcholine membranes would be its influence on the permeability of the vesicles. For example, it has been shown that incorporation of cholesterol into DMPC vesicles progressively reduces the leakage of carboxyfluorescein (CF) up to 30 mol% sterol [41], whereas N-dodecanoyl derivatives of amino acids such as glycine, valine, leucine and phenylalanine did not alter the permeability at low concentrations but led to complete leakage at concentrations close to their critical micellar concentrations [42]. The effect of incorporating NASTs on the permeability of phosphatidylcholine membranes can be assessed by monitoring the kinetics of the leakage of fluorescent probes such as CF or riboflavin that is loaded inside the vesicles [43,44].…”
Section: Computational Studies On the Molecular Packing Of Nastsmentioning
confidence: 99%